A simple iterative geometry-based interface-preserving reinitialization for the level set method. Issue 9 (21st October 2019) - Zhao, Lanhao; Zhang, Hairong; Mao, Jia; Zhu, Hanyue; Peng, Dawei; Mu, Kailong
Abstract : The iterative reinitialization, as an important process for the standard level set method, is flexible and straightforward in large-scale computing but has problems of interface movement and serious mass loss. Thus a simple iterative geometry-based interface-preserving reinitialization is proposed to reconstruct a signed distance function (SDF) while fixing the interface location with the combination of the external and internal iterations. The external iteration is used to restore the nature of the SDF. And the internal iteration firstly determines displacement errors of zero-level-set interpolation points via the geometric position of the interface, then the errors are redistributed iteratively to adjacent nodes until moving zero-level-set interpolation points are driven back to their original positions. The novel approach performs excellent mass conservation and shape preservation without sacrificing the simplicity of the iterative reinitialization. The accuracy and efficiency of the proposed method are validated with typical stationary interface examples and well-known benchmark cases.